SULAM KARAWO: KONSTRUKSI IDENTITAS BUDAYA GORONTALO - Rahma tiah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
The idea of making karawo embroidery crafts after the successful escape attempt from the excessive oppression and confinement of Dutch colonialism made the life of the society become isolated. Since then karawo embroidery has been becoming the work of tangible culture and conserved as local wisdom which is manifested in creative industry activities. This article purposes to analyze construction processes of karawo embroidery crafts in keeping the karawo existence as the culture based industry until of facing change orientation from the cultural symbol to commercial activity, which has moved the work pattern from sideline works to permanent works. This study used phenomenology method in digging the meaning of latent indications using interviews techniques to the karawo artisans, government, entrepreneurs. Collected empirical data are analyzed with using theoretical framework of social action theory to understand the formal rationality of actors that involved in the conservation, development and sustainability of karawo embroidery crafts industry. This study produces a typology of informants’ rational action (formal, substantive, theoretic, and practical) in constructing karawo embroidery sebagai culture identity,because has dimention: religion, social, culture and economicin the contemporary life reality.